Fusions of a carbohydrate binding module with the small cationic hexapeptide RWRWRW confer antimicrobial properties to cellulose-based materials - Barbosa, Mariana (2022)
The emergence of antibiotic-resistant bacteria is a critical worldwide healthcare problem. In the specific case of wound care, new and effective alternatives to currently available solutions are urgently needed. Cellulose-based dressings, for example, could be made more attractive if rendered antimicrobial. This work proposes a new strategy to modify cellulose-based materials with the short antimicrobial hexapeptide MP196 (RWRWRW - NH 2 ) that relies on a biomolecular recognition approach based on carbohydrate binding modules (CBMs). Specifically, we focused on the modification of hydrogels, paper, and microfibrillated cellulose (MFC) with fusions of the CBM3 from Clostridium thermocellum ( C. thermocellum ) with derivatives of MP196. The fusions are prepared by promoting the formation of a disulfide bond between Cys-terminated derivatives of MP196 and a CBM3 that is pre-anchored in the materials. The CBM3MP196-modified materials displayed antibacterial activity against Escherichia coli ( E. coli ), Pseudomonas aeruginosa ( P. aeruginosa ) and Staphylococcus aureus ( S. aureus ) that was significantly higher when compared with the activity of materials prepared by physical adsorption of MP196. The biomolecular strategy provides a more favorable orientation, exposure, and distancing of the peptide from the matrix. This versatile concept provides a toolbox for the functionalization of cellulose materials of different origins and architectures with a broad choice in peptides. Functionalization under mild biological conditions avoids further purification steps, allowing for translational research and multiple applications as drug delivery systems, scaffolds for tissue engineering and biomaterials.